2008
DOI: 10.1152/ajprenal.00604.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic candesartan alters expression and activity of NKCC2, NCC, and ENaC in the obese Zucker rat

Abstract: The obese Zucker rat reportedly has increased activity of the intrarenal renin-angiotensin-aldosterone system, which conceptually could contribute to elevated salt sensitivity and blood pressure (BP). Our aim was to determine whether there was increased angiotensin II type 1 receptor (AT(1)R)-mediated upregulation of expression or activity of the bumetanide-sensitive Na-K-2Cl cotransporter, the thiazide-sensitive Na-Cl cotransporter (NCC), and/or the epithelial sodium channel (ENaC) in obese vs. lean Zucker ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 40 publications
(62 reference statements)
6
32
1
Order By: Relevance
“…Similar to previous studies (1,28,39), expression levels of the ENaC subunits did not change in synchrony with one another. Levels of ␤-ENaC were reduced in the kidneys of HFD-fed mice, whereas expression of the other subunits was unchanged.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to previous studies (1,28,39), expression levels of the ENaC subunits did not change in synchrony with one another. Levels of ␤-ENaC were reduced in the kidneys of HFD-fed mice, whereas expression of the other subunits was unchanged.…”
Section: Discussionsupporting
confidence: 89%
“…The natriuretic response to furosemide has been used by others as a marker of the in vivo activity of NKCC2 (18,28,38,40). Mice (14 wk old) were administered intraperitoneal injections of 16.5 mg/kg furosemide (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our initial review of this subject, multiple examples of non-coordinate regulation of ENaC subunit protein or message have continued to appear in the literature (22,23,(52)(53)(54). It seems likely that more than one mechanism is required to fully explain this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…We have clearly shown that chronic blockade of the angiotensin II (ANG II) type 1 receptor (AT1R) reduces blood pressure in both lean and obese Zucker rats (30). However, the effect of AT1R blockade on dopamine receptor regulation in these rats has not been tested.…”
mentioning
confidence: 99%